2020
DOI: 10.3390/coatings10100912
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Barkhausen Noise Emission in Steel Wires Subjected to Different Surface Treatments

Abstract: Steel rope wires represent the main bearing components of bridges whose long-term operation depends on loading conditions, corrosion attack, and/or pre-stressing. Corrosion attack especially can remarkably reduce the effective cross-sectional area, which in turn over-stresses the wires and redistributes stress to the neighboring wires. The premature collapse of many bridges is very often caused by wire rupture as a result of their poor corrosion protection. For these reasons, various processes—such as galvaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, rupture of certain components in the structure can redistribute the stress to the neighboring regions and accelerate its collapse [12,13]. In order to improve the corrosion resistance of bridges made of steels, their surface is coated by protective multilayers of variable thickness and composition [14,15]. Due to the quite large dimensions of bridges and the corresponding steel components (being welded together), deposition of these layers is carried out by hand using spraying systems or brushes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rupture of certain components in the structure can redistribute the stress to the neighboring regions and accelerate its collapse [12,13]. In order to improve the corrosion resistance of bridges made of steels, their surface is coated by protective multilayers of variable thickness and composition [14,15]. Due to the quite large dimensions of bridges and the corresponding steel components (being welded together), deposition of these layers is carried out by hand using spraying systems or brushes.…”
Section: Introductionmentioning
confidence: 99%
“…The nitriding process produces the thin nitriding layer and underlying diffusion layer, which decreases MBN [ 16 , 17 ]. MBN decreases along with the increasing thickness of the non-ferromagnetic layer on the surface (and/or hard ferromagnetic) [ 16 ] as a result of superimposing effects clearly explained in previous studies [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 92%
“…Magnetic Barkhausen noise (MBN) has already been reported as a suitable technique for similar purposes [ 12 , 13 ]. It was reported that MBN can provide information about the Zn galvanizing process of wires [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I the Barkhausen noise method relies on observing the magnetization process, which causes the dipoles to rotate [14][15][16]. If the material contains inhomogeneities, the process of domain wall shifting will be disrupted.…”
Section: Introductionmentioning
confidence: 99%